2014
DOI: 10.1093/gbe/evu262
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Diversification in Strains of Rickettsia felis Isolated from Different Arthropods

Abstract: Rickettsia felis (Alphaproteobacteria: Rickettsiales) is the causative agent of an emerging flea-borne rickettsiosis with worldwide occurrence. Originally described from the cat flea, Ctenocephalides felis, recent reports have identified R. felis from other flea species, as well as other insects and ticks. This diverse host range for R. felis may indicate an underlying genetic variability associated with host-specific strains. Accordingly, to determine a potential genetic basis for host specialization, we sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
94
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(108 citation statements)
references
References 128 publications
(206 reference statements)
14
94
0
Order By: Relevance
“…Even greater genetic divergence is evident for R. felis , the etiological agent of a typhus-like flea borne rickettsiosis, whose genome is overrun by mobile genetic elements. Despite coding for ~1600–1800 ORFs, only 300 of these belong to the core set of genes shared by other rickettsial species14. It has also been suggested that typhus group genomes have a faster divergence rate in comparison to spotted fever group (SFG) species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even greater genetic divergence is evident for R. felis , the etiological agent of a typhus-like flea borne rickettsiosis, whose genome is overrun by mobile genetic elements. Despite coding for ~1600–1800 ORFs, only 300 of these belong to the core set of genes shared by other rickettsial species14. It has also been suggested that typhus group genomes have a faster divergence rate in comparison to spotted fever group (SFG) species.…”
Section: Discussionmentioning
confidence: 99%
“…R. conorii genome harbors a single chromosome of 1268755 bp encoding for 1578 protein coding genes, 9 pseudogenes, 33 tRNAs, 2 rRNAs, and contains ~32% intergenic region910. This relatively high percentage of non-coding region in R. conorii and other rickettsial genomes has traditionally been considered to be the ‘junk DNA’ or defunct genes resulting from reductive evolution and pseudogenization711121314. However, recent advances in computational bioinformatics and bacterial molecular genetics have led to the appreciation that the intergenic regions, in addition to harboring transcription factor binding sites and mobile genetic elements, encode for small non-coding RNAs involved in the regulation of target genes.…”
mentioning
confidence: 99%
“…gambiae , the role that infected mosquitos play in the epidemiology of R. felis infections in humans is unknown. In addition to these aforementioned blood-feeding arthropods, R. felis has also been cultured from the nonhematophagous book louse ( Liposcelis bostrychophila ),41 where its genetic diversity, compared with isolates obtained from other arthropods, is surprisingly great 42. Finally, R. felis DNA has even been detected in ape feces43—the implications of this finding are yet to be elucidated.…”
Section: Rickettsia Felis: Unresolved Issuesmentioning
confidence: 99%
“…Rickettsia akari, the causative agent of Rickettsialpox, was formerly placed into the SFG. However, current genomic studies reclassified this organism together with R. australis and R. felis into the TRG [4,5]. This mite-borne pathogen is usually transmitted to humans by a rodent mite Liponyssoides sanguineus [6,7].…”
Section: Introductionmentioning
confidence: 99%